Yale journal of international affairs
The Yale Journal of International Affairs (YJIA) is a biannual journal that seeks to bridge the gap between academia and the policy world. YJIA publishes articles, interviews, and op-eds by academicscholars, think tanks, policy practitioners, and advanced graduate students on international affairs topics with implications for policy.